1-Chloroacetyl-3-isopropyl-r-2,c-6-diphenylpiperidin-4-one - Ravichandran, K. (International Union of Crystallography, 2010)
In the title compound, C(22)H(24)ClNO(2), the piperidine ring adopts a distorted boat conformation. The dihedral angle between the two phenyl rings is 83.2 (1)°. In the crystal, the molecules are linked into chains running along the b axis by C—H⋯O hydrogen bonds. The Cl atom of the chloroacetyl group is disordered over two positions with occupancies of 0.66 (2) and 0.34 (2).